2013
DOI: 10.1094/pdis-05-12-0506-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Xanthomonas campestris pv. campestris as the Causal Agent of Black Rot on Oilseed Rape (Brassica napus) in Serbia

Abstract: In September 2010, leaves of oilseed rape (Brassica napus L.) with v-shaped, necrotic lesions on the leaf margins surrounded by yellow halos were collected. Symptoms were observed on the domestic cultivar Slavica (IFVC, Novi Sad) located in the Bačka region, Vojvodina, Serbia, from a 3-ha field. Average disease incidence on 3-month-old plants was 45% (15 to 75%). Diseased leaves were rinsed in sterilized distilled water (SDW) and dried at room temperature for isolations. Leaf sections taken from the margin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…The results confirm the genetic heterogeneity among Xcc isolates that was established by Popovi c et al (2013a), where two major clusters of Serbian Xcc isolates from broccoli (first), kale (first) and cabbage (second) isolated in 2010 were revealed using GTG 5 and ERIC rep-PCR primers. Subsequently, ERIC and GTG 5 proved to be useful tools for fast estimation of pathovar diversity within 10 Serbian oilseed rape Xcc strains, also isolated in 2010, separating them into two (98% similarity) and three (92% similarity) groups, respectively (Popovi c et al, 2014), thereby anticipating the differences at the genetic level obtained in the present study with isolates obtained 4 years later. In the study of Singh et al (2011), rep-PCR (REP-, BOX-and ERIC-PCR) oligonucleotide primers also showed an ability to separate five different groups of Xcc isolates from different Brassica cropscauliflower, cabbage, broccoli, kohlrabi and turnipfrom the northern region of India, indicating the presence of genetic diversity within this X. campestris pathovar.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…The results confirm the genetic heterogeneity among Xcc isolates that was established by Popovi c et al (2013a), where two major clusters of Serbian Xcc isolates from broccoli (first), kale (first) and cabbage (second) isolated in 2010 were revealed using GTG 5 and ERIC rep-PCR primers. Subsequently, ERIC and GTG 5 proved to be useful tools for fast estimation of pathovar diversity within 10 Serbian oilseed rape Xcc strains, also isolated in 2010, separating them into two (98% similarity) and three (92% similarity) groups, respectively (Popovi c et al, 2014), thereby anticipating the differences at the genetic level obtained in the present study with isolates obtained 4 years later. In the study of Singh et al (2011), rep-PCR (REP-, BOX-and ERIC-PCR) oligonucleotide primers also showed an ability to separate five different groups of Xcc isolates from different Brassica cropscauliflower, cabbage, broccoli, kohlrabi and turnipfrom the northern region of India, indicating the presence of genetic diversity within this X. campestris pathovar.…”
Section: Discussionmentioning
confidence: 51%
“…Host many cultivated cruciferous crops (Popovi c et al, 2013a(Popovi c et al, , 2014. In the light of its destructive potential, 147 isolates collected from seven brassicas (broccoli, cabbage, cauliflower, collard greens, kale, kohlrabi and winter oilseed rape) were subjected to examination of their genetic and pathogenic features in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…campestris (Pammel) Dowson (Xcc), foi descrita pela primeira vez por Garman em 1890 (ALVAREZ, 2000). A partir de então, esta doença vem sendo relatada em todas as regiões do mundo onde há o plantio de brássicas (ALVAREZ;CHO, 1978;THAVEECHAI, 1983;MASSOMO et al, 2003;MIRIK et al, 2008;JENSEN et al, 2010;POPOVIĆ et al, 2013) e tem causado perdas de produtividade e de qualidade dos produtos (VILLETH et al, 2009).…”
Section: Podridão Negra (Xanthomonas Campestris Pv Campestris)unclassified